(untitled) (Research, Society and Development, 2020)
The research aimed to investigate the thematization of Cultural Studies in the production of knowledge in Physical Education from periodicals indexed in the Portal de Periódicos Capes. Methodologically, documentary analysis was performed on the referred platform, which led to the finding of 20 articles that pointed to the proposal to be investigated. From the analyzes, the following categories were constructed: school and curriculum; training and university; gender and sexuality; and, media studies. As a result, it was possible to identify that the assumptions of Cultural Studies in the field of Physical Education emerge as a field that helps in the understanding of different identities that make up different bodily manifestations.